Resolution of Election Disputes for DPD Members Through Administrative Court Decisions Based on Law No. 7 of 2017 on General Elections (A Case Study of the DPD in West Sumatera Province) - Juliansyah, Ali Akbar; Harahap, Mhd. Yadi (Journal of Law, Politic and Humanities, 2024)
This research aims to analyze the Jakarta Administrative Court Decision No. 600/G/SPPU/2023/PTUN.JKT related to the election dispute of DPD (Regional Representative Council) members in 2023, from the perspective of Law No. 7 of 2017 on General Elections and fiqh siyasah (Islamic political jurisprudence). The focus of the dispute is the alleged violations by the General Election Commission (KPU) in the process of establishing the permanent voter list and determining the election results. This study employs a normative approach with a case study to address how election disputes for DPD members are resolved through Administrative Court decisions. The analysis reveals that the Jakarta Administrative Court Decision has integrated principles of justice and transparency as outlined in fiqh siyasah, and complies with the legal provisions of Law No. 7 of 2017. However, the study also highlights some challenges in enforcing accountability and transparency by the election organizers. This decision has strategic implications for governance and strengthening democracy in Indonesia, particularly within the context of Islamic constitutional law.